RISK: THE PERCEPTIONS OF THE RIVERSIDE COMUNITY OF SINOS RIVER IN RELATION TO THE USE OF AGROCHEMICALS - Rambow, Camila; Panichi, Valesca Beatriz Streppel; Figueiredo, João Alcione Sganderla (Revista Eletrônica em Gestão, Educação e Tecnologia Ambiental, 2014)
The changes generated by industrial development and population growth, led to an adaptation of food production. The use of pesticides in crops increases production and profitability. In one hand it helps the production, but there are risks of pollution. As a result of this scenario we propose a reflection across the risk perception of the riverside community of Vale do Rio dos Sinos regarding the use of pesticides and health. Overall, 89 questionnaires addressing issues on the use of pesticides, the health of handlers and also against environmental damage were applied. The results of this survey indicate that 38.2 % of respondents agree completely that agricultural production is possible without the use of pesticides and insecticides, 73.9 % completely agree that the chemicals cause damage to health, there is a 82 % need to use chemicals in their work. However 86.5 % believe that they do not offer risk to the environment and 7.9 % reported having health problems related to the use of pesticides in farming. The analysis of this study is through theories of risk society proposed by Douglas, Giddens, Beck and relations of representation proposed by Goffman.